Effectiveness of Flipbook Media on Children’s Knowledge and Behavior in Nutritious Food Consumption: School-based Intervention - Fatimah, Siti; Paramitha, Dewi Setya; Hamidah, Jamiatul; Rahayu, Suci Fitri; Bayu Rezki, Muhammad; Mawaddah, Annida; Hikmalia, Nur (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2026)
Background: childhood is an important stage of development. Non-fulfillment of nutrition in childhood has an impact on the health status of future generations. The use of Banjar-language flipbook educational media is one innovation that can be employed to enhance knowledge and change behavior in a more positive way. Purpose: exploring the effectiveness of using digital innovation and media nutrition education in the form of flipbooks, integrating local culture, to improve elementary school students’ knowledge and behavior regarding balanced nutrition. Methods: a one-group pretest-posttest pre-experimental design study was conducted with students (n=97) from two primary schools in Banjarmasin, South Kalimantan, to evaluate the effectiveness of the flipbook. Data were collected from July to August 2025 and included characteristics of respondents and the effects on knowledge and behavior regarding food nutrition. Data were analyzed using SPSS version 25. Descriptive statistics were used to summarize respondents’ characteristics. The Wilcoxon test was used to compare pretest and posttest scores of knowledge and behavior. A p-value of < 0.05 was considered statistically significant Results: of the 97 respondents, 57 respondents (58.79%) had good knowledge in the category, and 64 respondents (65.98%) had quite positive behavior. After receiving health education and access to flipbooks monitored by observation sheets, 77 respondents (79.38%) were in the “good knowledge” category, and 77 respondents (74.23%) showed very positive behavior Conclusion: the results of this study indicate that there is an increase in knowledge and behavior change in a positive direction after receiving nutrition education through flipbooks in the Banjar language integrated with Free Nutritious Meals (MBG) program in primary schools. The flipbooks will be integrated into the primary school curriculum